PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 016 BASILAM BARU - ', Kamaruddin; Alpusari, Mahmud Alpusari Mahmud; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This research represent the Research of Class Action (CAR) conducted to increase result of learning student of class of IV SDN 016 Basilam Baru by applying model the study of co-operative of type of Group Investigation (GI). This Research is conducted at April 2014 executed by 2 is cycle. this Subjek Research is student of class of IV SDN 016 Basilam Baru amounting to 28 one who is made by a data source. Instrument of data collecting of at this research is sheet of activity perception learn and student and also result of learning. Mean of result of learning previous student that is 58,2 from 28 complete student people only 6 completely is klasikal 21,4% while student which is not complete 22 people completely is klasikal 78,6%. At this research is presented by a activity percentage learn and student and also result of daily restating of cycle of I and cycle II. Activity Percentage learn at cycle of I and II is 58,4% mounting to become 79,2%. percentage of student Activity of at cycle of I and II is 52,1% mounting to become 81,3% Mean of result of learning student of at cycle I is 67,5 from 28 student, complete 17 people with the percentage 60,7% and which is not complete 11 people with the percentage 39,3%. Mean of result of learning student of cycle II is 88,5 from 28 one who complete 28 people with the percentage 100%. Inferential thereby that this research hypothesis that is if applied by model of study of co-operative of type of Group Investigation (GI) if can improve the result learn the student of class of IV SDN 016 Basilam Baru is accepted. Keywords : Model The Study of Co-Operative of Type of Group Investigation, Result of Learning IPS.